Neutralising antibodies and protection from progression to severe COVID-19: A meta-analysis - Karen M. Elias; Ainslie Mitchell; Eva Stadler; Timothy E. Schlub; Shanchita R. Khan; Claire Xue; Stephen J. Kent; Deborah Cromer; Miles P. Davenport; David S. Khoury (PLOS Medicine, 2026)
Background Vaccine-induced neutralising antibodies are a well-established correlate of protection against acquisition of COVID-19. Vaccine protection from severe COVID-19 remains high, although the role of neutralising antibodies and the contribution of other immune responses to protection from severe outcomes is less clear. Improving understanding of how vaccines prevent severe outcomes is important for future vaccine development. Methods and findings Here we undertake a systematic search of the literature to obtain estimates of vaccine protection against progression from SARS-CoV-2 infection to severe COVID-19 (hospital or ICU admission). We aggregate results from 25 published clinical studies of vaccine protection from progression to severe outcomes in people with SARS-CoV-2 infection. We match this clinical data to data from 301 studies of post-vaccination neutralisation titres induced by various vaccines against different SARS-CoV-2 variants from the publicly available Stanford University Coronavirus antiviral and resistance database. We then synthesise the data using meta-regression. Neutralising antibody titres were found to be associated with vaccine protection against progression to severe COVID-19 (relative risk (RR) 0.57 per 10-fold increase in GMT, 95% CI [0.51,0.64], p < 0.001). We found that the protection against progression provided by vaccination was higher than that provided by therapeutic passive administration of antibodies, when used to treat individuals with confirmed infection. The main methodological limitations were the fact that neutralisation titres and clinical outcomes were measured in different studies, and the possibility of unmeasured confounding. Conclusions Together, this work suggests that vaccine-induced neutralising antibodies are correlated with protection from progression to severe COVID-19 and can account for at least a partial mechanistic role in this protection. However, a protection gap remains between the high levels of protection against progressing to severe COVID-19 afforded by vaccination, compared to that afforded by therapeutic administration of antibodies, suggesting other immune responses may also play a role.